1992
DOI: 10.1007/bf02193926
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of some non-conventional plant foods of India

Abstract: Thirteen non-conventional foods including fruits, leaves and grains consumed in various parts of the Indian subcontinent were analysed for their nutritional value. Khejri beans (Prsopsis cineria), Pinju (Capparis decidua) and Kachri (Cucumis species) contained considerable amounts of protein (15-18%). Kachri was rich in fat (13%). Bhakri (Tribulus terristris), Gullar (Ficus glomerata) and Peehl (Salvadora oleoides) were found to be rich sources of calcium; Gullar contained about 15 times the amount of calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 3 publications
5
30
2
Order By: Relevance
“…Third, figs contained high concentrations of inorganic material, presumably minerals (ash), and contributed 44% of the monkeys' total intake of inorganic material. Figs are extremely rich sources of available calcium (Duhan et al 1992;O'Brien et al 1998;Ruby et al 2000;Silver et al 2000;Wendeln et al 2000), which is critical for maintenance and reproduction (Robbins 1993). We suggest that all of these factors contributed to figs being the staple food of spider monkeys in La Chonta.…”
Section: Discussionmentioning
confidence: 70%
“…Third, figs contained high concentrations of inorganic material, presumably minerals (ash), and contributed 44% of the monkeys' total intake of inorganic material. Figs are extremely rich sources of available calcium (Duhan et al 1992;O'Brien et al 1998;Ruby et al 2000;Silver et al 2000;Wendeln et al 2000), which is critical for maintenance and reproduction (Robbins 1993). We suggest that all of these factors contributed to figs being the staple food of spider monkeys in La Chonta.…”
Section: Discussionmentioning
confidence: 70%
“…It could be due to the wide margin of safety that B. diffusa is used as a non-conventional food consumed in various parts of Indian sub-continent. 10) Table 1 shows the effect of various doses of B. diffusa aqueous extract on weekly food and fluid intake. The extract increased the food intake of the animal compared to control at p < 0.05 throughout the three weeks of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…5 and 1.1 mg/100 g, for leaves and buds, respectively). Other studies reported that leaves and fruits of Capparis decidua contained 21 and 2.45 mg/100 g of β-carotene, respectively [29,30]. These differences might be related to different geographic climatic conditions or may also reflect genetic variability.…”
Section: Carotenoids Contentmentioning
confidence: 99%